PELATIHAN PEMBUATAN WEBSITE E-COMMERCE PADA MAHASISWA PASCASARJANA MAGISTER MANAJEMEN UNIVERSITAS OTTOW GEISSLER PAPUA - Bonifasia E. Bharanti; Mingsep R. Sampebua (JURNAL PENGABDIAN PAPUA, 2020)
The objective of dedication is to deliver the knowledge and technology throught training in making e-commerce website. The activity can improve the ability and knowledge of graduate students as the partners in the online marketing system and the student can practice to create an e-commerce website by using wordpress.  E-commerce website application is an online business service that is needed to conduct purchases, sales, or exchange of product services and information services throught the internet network. The dedication activities include several stages, namely identification of partner needs, presentation of training materials to partners and practice of making e-commerce website. Keywords: Wordpress, E_commerce, Website training, MM UOG, Dedication